Body Mass Index and Hypertension in Pregnant Women - Wiratmo, Puji Astuti; Sutandi, Aan (Faculty of Nursing and Midwifery, Binawan University, 2024)
The incidence of hypertension in pregnancy is still a big concern in health care setting. This condition can cause further complication that could endanger mother and fetal condition. Hypertension in pregnancy can lead to cardiovascular disease, diabetes, cerebrovascular diseases, and death. There are several factors affecting hypertension on pregnant wome, including overweight and obesity. BMI can be used to identify nutritional status as well as to monitor weight gain in pregnant mother. This study was aimed to identify the relationship between BMI and hypertension in pregnancy. The data collection was conducted on 104 pregnant women in Matraman Primary Health Care, East Jakarta. BMI was calculated by using body weight and body height. While hypertension was identified through an increase in blood pressure measurement whereby systole was above 140 mmHg and diastole was above 90 mmHg. The data was analyzed using chi square test with significancy level p <0.05. The result of the study showed that there was a significant relationship between BMI and hypertension on pregnant women (p 0,001). Monitoring of BMI is critical in pregnant mother particularly on those who have high BMI. It is important that all health care professionals provide significant efforts to manage obesity and to overcome hypertension on pregnant women to reduce the morbidity and mortality on pregnant women.